Active perception: sensorimotor circuits as a cortical basis for language - Pulvermüller, Friedemann; Fadiga, Luciano (Nature reviews. Neuroscience, 2010)
Pulvermüller and Fadiga address the much discussed question of whether speech comprehension depends on activation of cortical motor areas. Reviewing data from neuroimaging, brain stimulation, lesion and computational studies, they conclude that action and perception circuits have interdependent roles in language comprehension. Action and perception are functionally linked in the brain, but a hotly debated question is whether perception and comprehension of stimuli depend on motor circuits. Brain language mechanisms are ideal for addressing this question. Neuroimaging investigations have found specific motor activations when subjects understand speech sounds, word meanings and sentence structures. Moreover, studies involving transcranial magnetic stimulation and patients with lesions affecting inferior frontal regions of the brain have shown contributions of motor circuits to the comprehension of phonemes, semantic categories and grammar. These data show that language comprehension benefits from frontocentral action systems, indicating that action and perception circuits are interdependent.